Review of prescribing information for influenza vaccines for pregnant and lactating women - Proveaux, Tina (Vaccine, 2016)
Information provided by most influenza vaccine manufacturers do not reflect the recommendations of WHO and/or national public health advisory groups with regard to the use of influenza vaccines in pregnant or lactating women. The majority of vaccines contain precautionary language which could discourage use in pregnant women and some include stronger language discouraging or contradicting use in pregnant or lactating women. Regulators and manufacturers should regularly assess the language of pregnancy and lactation sections in product information for vaccines and include information from national public health advisory groups regarding use by pregnant or lactating women and data from relevant studies.